Feasibility of lignin-containing cellulose nanofibrils derived from oil palm empty fruit bunch in enhancing the properties of non-wood handsheets - Mhd Idris, Farah Nabila; Ariffin, Hidayah; Md. Tahir, Paridah; Ibrahim, Rushdan (Elsevier, 2024)
The addition of nanocellulose has been reported to improve the properties of handsheet, mainly the mechanical properties. Nevertheless, nanocellulose addition slows down the water drainage during handsheet making due to the filling effect and increase in fibre bonding, which results in the reduction of handsheet making productivity. In this research, the use of nanocellulose containing residual lignin was hypothesized to improve the productivity in comparison to pure nanocellulose. Lignin-containing cellulose nanofibrils (LCNF) samples having different lignin content were prepared from oil palm empty fruit bunch (OPEFB) through controlled multi-step bleaching process. The LCNF samples were then used in handsheet making with LCNF loading of 1, 2, 4, and 8 wt%. Three LCNF samples were successfully prepared (LCNF-1, LCNF-2 and LCNF-3) with different lignin content at 7.7%, 2.8%, and 0.5%, respectively. LCNF-2 and LCNF-3 had the average width of 31 nm, while LCNF-1 exhibited some portions of incomplete fibrillation which could be attributed to the presence of lignin. The addition of LCNF increased the drainage time compared to the one without LCNF (control), and the drainage time increased with the increase in LCNF loading. Overall results indicated that the addition of 4 wt% LCNF-2 contributed to the best combination in terms of drainage time, tensile index and tear index at 11.3 s, 38.1 Nm/g, and 9.3 mN.m2/g compared to the control sample (8 s, 31.8 Nm/g, and 7.4 mN.m2/g respectively). LCNF-3 gave comparable results, however from sustainability point of view, it is less favoured as it requires more bleaching chemicals to be produced. Findings from this research highlight the importance of lignin in improving the productivity and properties of nanocellulose-incorporated handsheet.